Os ambientes digitais e as práticas de leitura: uma análise de atividades do portal do professor do MEC - Valeria Ribeiro de Castro Zacharias (2013)
This study presents an analysis of eleven classes plans published in Espaço da Aula (Classroom Space) at Portal do Professor do MEC. Their goal was to identify how the elementary school teachers of Basic Education elaborate proposals to introduce digital technologies to develop reading skills in the perspective of literacy. To proceed the interpretation the conceptions of teaching and learning were considered, as well as conceptions of language and the underlying notions of literacy described by teachers. The choice of the Portal do Professor do MEC was due, mainly, to this site be an environment created to foster teachers of basic education to use of digital technologies and because it is proposed by the federal government, which, supposedly, will guarantee its legitimacy and reliability. Classroom Space, (Espaço da Aula), one of the links available on the Portal, brings suggestions of classes developed by teachers from various school systems in Brazil, providing a broad universe of research on their discourses and practices. The integration of digital technologies in education requires a new look at the processes of teaching and learning how to read, which are replaced by the screen as support of multiple texts that include a set of languages to read objects, such as images, sound, movement written and verbal. In addition, changes in the forms of communication, caused by the introduction of computers in the contexts of everyday life, are demanding from educational institutions to teach practices that contribute effectively to the training of students, who need to know how to act in the universe of a collaborative contemporary society. The results of the analysis found that, in spite of advances in the theoretical understanding of learning as a construction and of language as social and rhetorical activity, the recommendations presented in the analyzed activities contribute little to develop digital literacy. The classes plans analyzed reveal that teaching reading skills still preserves the perspectives of traditional methodologies adopted for the print environment, even when the content selection include genres of digital media. This means that the pedagogical approach with the new language practices do not incorporate the mechanisms and new navigation gestures involved in reading hypertext digital.